1995
DOI: 10.1016/s0022-5347(01)66881-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life: Radical Prostatectomy Versus Radiation Therapy for Prostate Cancer

Abstract: Radical prostatectomy and external beam radiotherapy have comparable impact upon quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
1
3

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(109 citation statements)
references
References 21 publications
9
96
1
3
Order By: Relevance
“…17 This study did not assess generic domains of quality of life, but the researchers did report significant associations between symptoms and the physical domains of the Functional Living Index: Cancer, a cancer specific quality-of-life measure.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…17 This study did not assess generic domains of quality of life, but the researchers did report significant associations between symptoms and the physical domains of the Functional Living Index: Cancer, a cancer specific quality-of-life measure.…”
Section: Discussionmentioning
confidence: 94%
“…Prior studies that have reported results on the association between bowel symptoms and quality of life have not examined the impact across such a wide range of domains. 3,11,17 Using a single question (After your prostate carcinoma treatment, do you feel your overall quality of life is: better than before/same as before/worse than before? ), Kao and colleagues 3 found that incontinence and impotence were significant predictors of overall health status (OR, 0.41 and 0.34, respectively for better or same vs. worse).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, there has been increasing recognition that cancer therapy significantly impacts on patients' quality of life (QOL). [4][5][6][7][8][9][10] For patients, survival rate is not the sole factor influencing choice of treatment. A treatment with a lower survival rate may be preferred if it conferred a life of superior quality.…”
Section: Introductionmentioning
confidence: 99%